PENGARUH AUGMENTED REALITY (AR) TERHADAP KEMAMPUAN SELF-ASSESSMENT SISWA DALAM PEMBELAJARAN MATEMATIKA - Indah Wahyuni; Nabila Wardah Nafi'ah; Ulfa Dina Novienda (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2025)
This study aims to investigate how the use of Augmented Reality (AR) impacts students' self-assessment skills in mathematics learning. Students are given the ability to assess themselves, which is very important to help them become independent learners and critical thinkers. A quasi-experimental design with a pretest-posttest control group was used. All 72 grade XI students in the sample were divided into experimental and control groups. Self-assessment tests and questionnaires were the tools used. The results of the analysis showed that, compared to the control class, students' self-assessment skills in the experimental class increased significantly. The results showed that AR was able to increase students' awareness in assessing their own understanding; the experimental group had a higher average self-assessment. Based on these findings, it can be concluded that AR has a positive effect on students' self-assessment skills. Therefore, it is recommended that AR be incorporated into mathematics learning to support students' metacognitive skills.